2018
DOI: 10.1101/259119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A neural circuit arbitrates between perseverance and withdrawal in hungry Drosophila

Abstract: Highlights• Lack of reward stimulates perseverance, and not quitting.• Dopaminergic neurons previously implicated in aversive learning promote perseverance.• Sugar responsive octopaminergic neurons counteract perseverant odor tracking behavior through a downstream inhibitory neuron.• Computational modeling supports a simple neural circuit featuring antagonistic functions for dopamine and octopamine as tallies of expense and gain.peer-reviewed) is the author/funder. All rights reserved. No reuse allowed without… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Several recent studies agree with such a circuit. For example, activation of octopaminergic VPM4 neurons decreased GCaMP responses in MBON-g1pedc>a/b neurons [49] and activation of PAM-DANs decreased Ca 2+ transients in MBON-g4 in vivo [12]. In addition to MB-b'1, recent data from our group demonstrate neuropeptidergic modulation of other central DANs (PPL1) that project to the vertical MB lobes and also regulate duration of flight bouts [50].…”
Section: Activity In Pam-dans Reduces Gaba Release From Mbons To Suppmentioning
confidence: 76%
“…Several recent studies agree with such a circuit. For example, activation of octopaminergic VPM4 neurons decreased GCaMP responses in MBON-g1pedc>a/b neurons [49] and activation of PAM-DANs decreased Ca 2+ transients in MBON-g4 in vivo [12]. In addition to MB-b'1, recent data from our group demonstrate neuropeptidergic modulation of other central DANs (PPL1) that project to the vertical MB lobes and also regulate duration of flight bouts [50].…”
Section: Activity In Pam-dans Reduces Gaba Release From Mbons To Suppmentioning
confidence: 76%
“…Upwind orientation in walking flies appears to depend entirely on mechanical cues while upwind orientation during flight has been shown to be sensitive to visual cues ( Kennedy, 1940 ; Kennedy et al, 1981 ; van Breugel and Dickinson, 2014 ). Searching responses after odor offset have been observed in walking cockroaches ( Willis et al, 2008 ), and have been observed in adult flies following removal from food ( Dethier, 1976 ; Kim and Dickinson, 2017 ) but have until recently not been reported in flies in response to odor ( Sayin et al, 2018 ). The OFF response seems to play a role related to casting in flying insects, allowing the fly to relocate an odor plume once it has been lost, although the response we observed did not have any component of orientation orthogonal to the wind direction, as has been described in flight ( Kennedy and Marsh, 1974 ; van Breugel and Dickinson, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both this diverged preference and high activity of starved flies are known effects described in Drosophila spp. Starved flies move about more actively [87], have higher odour tracking perseverance [88] and a higher response rate when offered a single (food cue) choice [54,58] compared to fed flies. For D. melanogaster and Drosophila simulans , Turelli and Hoffmann (1988) showed in mark–release–recapture experiments that starved flies were less discriminating and prone to be attracted to inferior resources [89].…”
Section: Discussionmentioning
confidence: 99%